Global analysis of lysine ubiquitination by ubiquitin remnant immunoaffinity profiling - Xu, Guoqiang (2010)
Protein ubiquitination is a post-translational modification (PTM) that regulates various aspects of protein function by different mechanisms. Global profiling of PTMs usually relies on purification and sequencing of PTM-containing peptides from proteolytic digests. Characterization of ubiquitination has lagged behind that of smaller PTMs, such as phosphorylation and acetylation, largely because of the difficulty of isolating and identifying peptides derived from the ubiquitinated portion of proteins. To address this issue, we have generated a monoclonal antibody that can enrich for peptides containing lysine residues modified by diglycine, an adduct left at sites of ubiquitination after trypsin digestion. We use mass spectrometry to identify 374 diglycine-modified lysines on 236 ubiquitinated proteins from HEK293 cells, including 80 proteins containing multiple sites of ubiquitination. Seventy-two percent of these proteins and 92% of the ubiquitination sites do not appear to have been reported previously. Ubiquitin remnant profiling of the multi-ubiquitinated proteins proliferating cell nuclear antigen (PCNA) and tubulin α-1A reveals differential regulation of ubiquitination at specific sites by microtubule inhibitors, demonstrating the effectiveness of our method to characterize the dynamics of lysine ubiquitination.